Carbofuran metabolism and toxicity in the rat - Ferguson, Paul W.; Dey, Michael S.; Jewell, Sarah A.; Krieger, Robert I. (Fundamental and applied toxicology, 1984)
The influence of carbofuran metabolism on acetylcholinesterase inhibition has been defined after low dose (50 μg/kg, iv and oral) [ carbonyl- 14C]carbofuran exposures to male Sprague-Dawley rats. Red blood cell acetylcholinesterase (RBC AchE) inhibition (83% at 2 min, 37% at 15 min for iv and oral, respectively, with recovery by 3 hr), was correlated with carbofuran plasma concentrations ( r=0.97). Eight-hour sample collection indicated that ultimate carbofuran fate (41–47% 14CO 2, 14–15% urine, <1% feces, and 30–31% carcass) was independent of exposure route. Carbofuran absorption (peak plasma levels < 7 min), distribution, and elimination ( t 1 2 =29 ± 5 min ) occurred rapidly. 3-Hydroxycarbofuran, a significant oxidative metabolite of carbofuran with anticholinesterase activity, was rapidly formed and subject to enterohepatic circulation (plasma t 1 2 = 64 ± 5 min ). Results indicated that rapid RBC AchE recovery closely paralleled carbofuran metabolism and the primary in vivo disposition of 3-hydroxycarbofuran was metabolic conjugation.